Punishment (Theory of) - Rodríguez Horcajo, Daniel (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The theory of punishment is constituted by two elements that have been studied by the doctrine in an unequal way. In the first place, this theory tries to define what should be understood as ’punishment’, in order to differentiate it from other sanctions (formal or informal ones). Secondly, it deals with justifying, in abstract terms, a state intervention of such magnitude on the individual sphere, opting for absolute theories, for preventive theories or for some kind of intermediate position between one and the other.